Budidaya Ikan Cupang Dengan Metode Daun Belimbing - Febry Chrisdanty; Aulia Rahman Oktaviansyah; Dani Harianto (STIE Malangkucecwara, 2022)
The covid-19 pandemic has killed many businesses and incomes for the Slorok village community. The problem faced is the lack of capital. As a partner, the Slorok village community wishes to take advantage of the facilities they have in the form of a fish pond that can be used for betta fish breeding. The solution is to create a Betta Fish Cultivation Business. This situation requires all to keep their distance so that the hobby and activity that is highly recommended is betta fish cultivation. This hobby is growing and has many enthusiasts, and the price is increasing, so it can become one of the sources of income that can be initiated by the people of Slorok Village, Kromengan, Malang Regency. The method that will be used is a social and practical approach. The result of the implementation of this betta fish cultivation service program is that the training and practice have been carried out well by the service team and also partners. the Slorok village community as partners already have the knowledge and expertise to cultivate betta fish with star fruit. The provision of knowledge and skills in the application of betta fish cultivation is very helpful in efforts to produce quality betta fish products, so that it will improve the welfare of the local community. To be able to realize the things mentioned above, socialization and assistance are needed that can support the needs of betta fish farming.